Microstructure and properties of friction welding joint of Ti–45Al-8.5Nb-0. 2W-0. 2B-0. 02Y alloy. (September 2019) - Xu, Xiangjun; Lin, Junpin; Guo, Jian; Wang, Xin; Yu, Xinxin
Abstract: High Nb containing TiAl alloys have prospect to be used for turbo wheel and exhaust valve for vehicle engine. Friction welding is a suitable process for fabricating these components. For investigating the weldability of these alloys, cylindrical samples of Ti–45Al-8.5Nb-0.2W-0.2B-0.02Y (in at%) alloy with a diameter of 10 mm were welded by continuous drive friction welding process, and the microstructures and the mechanical properties of the joints were analyzed in this paper. The results showed that the weldability of the present alloy was very good. At parameters of rotational speed of 2400 r/min, friction pressure of 320 MPa, burn-off distance of 3 mm and upset pressure of 360 MPa, completely metallurgical bonding interfaces were obtained. The joint had a severely plastic deformation zone (SPDZ) with a biconcave lens geometry. The thicknesses of the center and periphery of SPDZ were about 40 μm and 800 μm, respectively. There existed a transition zone (TZ) between parent metal (PM) and SPDZ. SPDZ exhibited the deformation flow lines and had a randomly-oriented recrystallized duplex (DP) microstructure with the average grain size of 2.5 μm, in contrast, PM presented a nearly lamellar (NL) microstructure with a colony size of 150 μm. TZ showed a mixture microstructure combining deformed lamellar colonies and partially recrystallized grains. At room temperature, 750 °C and 800 °C, welding joints had better tensile properties than PM. Highlights: As-cast Ti–45Al-8.5Nb-0. 2W-0. 2B-0. 02Y alloy has good friction weldability. The joint had a severely plastic deformation zone with a biconcave lens geometry. Fine-grained DP microstructure of welding joint showed random orientation. Welding joint had better tensile properties than parent metal.